(untitled) (International journal of artificial intelligence, 2025)
In the context of accelerating global digitalization, Uzbek service sector companies are facing the need for a profound transformation of their innovation and investment strategies. Digital transformation is becoming a key factor in increasing competitiveness, reducing transaction costs, and accelerating innovation in segments such as financial services, logistics, education, healthcare, hospitality and tourism, and e-commerce. In 2023–2024, investment in digital service infrastructure in Uzbekistan increased by more than 32%, and the share of online platforms in total transaction volume reached 38%. Government programs (Digital Uzbekistan 2030, Digital Economy), as well as support from international financial institutions, are creating favorable conditions for capital inflows and the implementation of innovative technologies. Particular attention is paid to the development of artificial intelligence, big data, cloud services, and fintech solutions, which enable service sector companies to improve productivity, personalize customer experiences, and develop new business models. The development of digital financial instruments, including crowdfunding, venture capital, and public-private partnerships, plays a key role in facilitating the accelerated modernization of service industries. The scientific significance of this study lies in identifying patterns in the impact of digital transformation on the investment processes of service sector enterprises, as well as in identifying mechanisms for stimulating innovation. The practical value of this work lies in formulating recommendations for businesses and government on the effective use of digital technologies to attract investment and improve the sustainability of the service sector economy.